Monoclonal Antibodies Capable of Inhibiting Complement Downstream of C5 in Multiple Species - Zelek, Wioleta M.; Morgan, B. Paul (Frontiers in Immunology, 2020)
Better understanding of roles of complement in pathology has fuelled an explosion of interest in complement-targeted therapeutics. The C5-blocking monoclonal antibody (mAb) eculizumab, the first of the new wave of complement blocking drugs, was FDA approved for treatment of Paroxysmal Nocturnal Hemoglobinuria in 2007; its expansion into other diseases has been slow and remains restricted to rare and ultra-rare diseases such as atypical haemolytic uremic syndrome. The success of eculizumab has provoked other Pharma to follow this well-trodden track and made C5 blockade the busiest area of complement drug development. C5 blockade inhibits generation of C5a and C5b, the former an anaphylatoxin, the latter the nidus for formation of the pro-inflammatory membrane attack complex. In order to use anti-complement drugs in common complement-driven diseases, more affordable and effective therapeutics are needed. To address this, we explored complement inhibition downstream of C5. Novel blocking mAb targeting C7 and/or the C5b-7 complex were generated, identified using high throughput functional assays and specificity confirmed by immunochemical assays and surface plasmon resonance (SPR). Selected mAb were tested in rodents to characterise pharmacokinetics, and therapeutic capacity. Administration of a mouse C7-selective mAb to wildtype mice, or a human C7 specific mAb to C7-deficient mice reconstituted with human C7, completely inhibited serum lytic activity for >48 hr. The complex selective mAb 2H2, most active in rat serum, efficiently inhibited serum lytic activity in vivo for over a week from a single low dose (10mg/kg); this mAb effectively blocked disease and protected muscle endplates from destruction in a rat myasthenia model. Targeting C7 and C7-containing terminal pathway intermediates is an innovative therapeutic approach, allowing lower drug dose and lower product cost, that will facilitate the expansion of complement therapeutics to common diseases.